Ozone generation using electrical discharges : a comparative study between pulsed streamer discharge and atmospheric pressure glow discharge - 486106 Zolkafle Buntat (England : Loughborough University, 2005)
Thesis (Doctor of Philosophy (Electrical)) - Loughborough University, 2005